PhD: The Amazing Journey - Volume 3 - Cheng, Jack Kie (Penerbit UMPSA, 2024)
Greetings, fellow intellectual explorers, and welcome to the enthralling world of PhD: The Amazing Journey Volume 3. If you're reading this, you're either in the middle of a PhD project, thinking about starting one or perhaps seeking some real-life inspiration. Well, you're in the right place. Following the success of the first two volumes, Volume 3 returns with 12 brand-new narratives. These amazing storytellers received their doctoral degrees from distinguished local and international universities, and they are gathered here in this book to pen their own PhD journey. Within these pages are brilliantly written anecdotes that intertwine stories of realising one’s dream; overcoming disappointment, heartbreaks, loss and grief; confronting fear and anxiety; and dealing with stress and mental block, and overflowing excitement, happiness, gratitude and relief. These are also the stories of remarkable endurance, perseverance and conquering defeats, over and over again throughout the PhD voyage. Say no more, jom grab a cup of coffee and a box of chocolate, and let these stories ignite the fire in you, the drive of intellectual pursuit. Be inspired and may this little book be your trusted companion during your trials and turbulences. We wish you the best of luck and may PhD: The Amazing Journey Volume 3 we have the opportunity to collect your very own PhD story in our future PhD: The Amazing Journey series.